STUDY OF THE ELEMENTAL COMPOSITION OF THE AERIAL PART OF THE MEDICINAL PLANT POLPALA - Khasanova B.Z; Olimov N.K; Abdullaeva M.Yu; Sidametova Z.E; Rakhimova D.O (Western European Studies, 2024)
The paper presents the results of research work on the study of the elemental composition of the plant polpala (Aerva lanata (L.) Juss.), collected in the Namangan region. For this purpose, the mass spectral method of inductively coupled plasma was used. It has been established that the amount of elements such as sodium, nickel, magnesium, iron, cobalt, cadmium, and chromium in the plant is relatively high. Among the macroelements, the element calcium had the highest indicator (13.24%)
Keywords: plant polpala; elemental composition; mass spectral method of inductively coupled plasma